STRUCTURAL PERFORMANCE OF REINFORCED CONCRETE BUBBLE SLABS AFTER EXPOSING TO FIRE FLAME - Saud Salman Al-Gasham, Thaar (Journal of Engineering and Sustainable Development, 2015)
This paper presents the results of experimental program investigating the effect of fire flame (high temperature) on the structural performance of bubble slabs. The program consisted casting and testing nine specimens. The dimensions of the specimens were 270 X 500mm in plane and with two different thicknesses; 90 and 140mm. All specimens were cast with normal concrete of approximately 25 MPa compressive strength. Seven specimens were burnt using a diesel furnace and two specimens were kept without burning as controls. The test parameters were; the fire flame temperature (200, 500, and 800 oC), the cooling method is processed gradually by left the slabs in the air or suddenly by using water, the exposure time (1, 1.5, and 2 hours), and thickness of slabs (90 and 140mm). After cooling, the specimens were simply supported in one direction and tested under a uniform load applied gradually till failure. The test results showed that, the residual strength of specimens decreased from 71.8% to 21.6% and their central deflection increased with increasing the fire flame temperature from 200 to 800 oC and exposure time from 1 to 2 hours.